The impact of Using Twitter and Instagram to Promote Social Values among University Students - Almajali , Hussein K.; Owais, Delal F.; Majali, Areen A. Q. Bajes Al Jadeed; Tarawneh , Haya Hussien M.; Al Masri, Amaal A. (Journal of Ecohumanism, 2024)
The research aims to explore the impacts of students’ use of social media on values of citizenship and determine which of their needs are gratified: the need for personal identity, integration, and social interaction or feeling satisfaction. The other goal is to determine the university students’ expectations in the Arab world when using social networks. The research investigates the impact of using Facebook and Instagram in promoting Citizenship values among Arab students at Jordanian universities. The study’s findings indicate that social media promotes social ideals and enhances citizenship among Arab students at Jordanian colleges. The principal aim for students utilizing social media is social interaction, with a mean score of (4.20) and a standard deviation of (0.50), which is achieved by accessing information regarding university life, which has a mean of (4.10). The foremost citizenship value was respect for others and tolerance, with a mean of (4.30) and a standard deviation of (0.42). Meanwhile, active community involvement scored a high mean of 4.25. Social networks greatly contributed to values like citizenship with particular emphasis on respect for diversity - mean 4.40 and involvement in civic matters - mean 4.25. The encouragement of talks over social media about national issues scored 4.35. These findings show the positive influence of social media on enhancing the level of participation and community involvement among students.